(The Use of Natural Antioxidant Coconut Oil) - M Maman Rohaman; Solechan -; Derris Trismansyah; Ign Soeharto (Balai Besar Industri Agro, 1998)
The objective of this research is to study the effect of natural antioxidant such as clove and sesame seed on the reaction rate of coconut oil oxidation. The experimental procedure used the randomized block design factorial using two variables. The treatment chosen consists of coconut oil with clove antioxidant, coconut oil with sesame seed antioxidant, coconut oil with sesame seed plus clove antioxidant which each dosage 200 ppm and finally coconut oil without antioxidant (control). Those samples were analyzed at periodic intervals for oxidative deterioration. The parameter analysis consists of the perioxide number, free fatty acid, iod number,moisture content and oil clearness. The result indicate that the natural antioxidants (clove and sesame seed) are capable of preventing oxidative deterioration. Natural antioxidants give a very significant result on coconut oil quality, in the following order : coconut oil with clove antioxidant, coconut oil with sesame seed antioxidant, coconut oil with sesame seed plus clove antioxidant with the constant of reaction rate 0.15, 0.12 and 0.09.